Manejo de software de oficina y su aportación en el desarrollo de la gestión financiera de las secretarias del área contable de la Cooperativa de Ahorro y Crédito San Antonio de la ciudad de Vinces - Burgos Cortez, Jostyn Steven (2022)
The present case study lies in describing, and carrying out an analysis in reference to the topic: Management of office software and its contribution in the development of the financial management of the secretaries of the accounting area of the San Antonio Savings and Credit Cooperative. city of Vinces, whose purpose is to propose solutions to the problems presented in said study. For this, the deductive method was used through which relevant information was obtained that goes from the general to the particular, however, for the collection of information, a questionnaire was developed as an instrument, applied to the secretaries of the aforementioned place, with in order to collect and analyze the information obtained. It should be noted that the main objective of the research is to investigate how the management of office software contributes to the financial management of the secretaries of the accounting area. In the same way, it is important to highlight that the general objective of this research is to describe the importance of managing the different types of software in financial management, and for this reason, starting from this goal, the development of this study concluded through of the results obtained that; the management of these computer programs is basically that essential resource to apply because it makes it possible to carry out excellent financial management in the entities. In addition, with the deduction of the results obtained, it is to propose the implementation of training, so that in this way the secretaries strengthen their knowledge and skills